2021
DOI: 10.1021/acssuschemeng.1c01136
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Enriched Biomass-Activated Carbon Supported Platinum Nanoparticles as an Efficient and Durable Catalyst for Oxidation in Benzene

Abstract: Carbon materials have been widely utilized as supports in different catalytic reactions; however, it has been rarely reported that carbon supports were used in the catalytic oxidation of volatile organic compounds because they have no catalytic activity and poor catalytic stability compared to metal supports. Herein, fabricating optimal carbon supports to facilitate the catalytic oxidation of benzene has become a great concern of research. A novel activated carbon (biomass−HCO) was prepared from different wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 45 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…The XRD patterns indicate that the graphitic structure of the carbon-based catalysts is found by the existence of the broad diffraction peak approximately at 23°, which is the characteristic of the crystalline graphite (002) plane of graphitic carbon. , The other sharp peaks at about 26, 30, 32, and 44° are considered to be the crystallization of inorganic impurities, for example, silica after calcination of straw . Two peaks at 1348 and 1587 cm –1 are observed in the Raman spectra (Figure b), which are, respectively, attributed to the D-band and G-band for the typical characteristic Raman peaks of carbon. , The ratio of D-peak intensity to G-peak intensity ( I D / I G ) can be used to characterize the degree of defects in carbon. , After the introduction of N in CN-900, the defect degree increases by the fact that the I D / I G ratio increases from 1.88 in CN-900 to 2.06 in N/CN-900.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The XRD patterns indicate that the graphitic structure of the carbon-based catalysts is found by the existence of the broad diffraction peak approximately at 23°, which is the characteristic of the crystalline graphite (002) plane of graphitic carbon. , The other sharp peaks at about 26, 30, 32, and 44° are considered to be the crystallization of inorganic impurities, for example, silica after calcination of straw . Two peaks at 1348 and 1587 cm –1 are observed in the Raman spectra (Figure b), which are, respectively, attributed to the D-band and G-band for the typical characteristic Raman peaks of carbon. , The ratio of D-peak intensity to G-peak intensity ( I D / I G ) can be used to characterize the degree of defects in carbon. , After the introduction of N in CN-900, the defect degree increases by the fact that the I D / I G ratio increases from 1.88 in CN-900 to 2.06 in N/CN-900.…”
Section: Resultsmentioning
confidence: 91%
“…The XRD patterns indicate that the graphitic structure of the carbon-based catalysts is found by the existence of the broad diffraction peak approximately at 23°, which is the characteristic of the crystalline graphite (002) plane of graphitic carbon. 31,32 The other sharp peaks at about 26, 30, 32, and 44°a re considered to be the crystallization of inorganic impurities, for example, silica after calcination of straw. 33 Two peaks at 1348 and 1587 cm −1 are observed in the Raman spectra (Figure 3b), which are, respectively, attributed to the D-band and G-band for the typical characteristic Raman peaks of carbon.…”
Section: Catalyst Characterizationsmentioning
confidence: 99%
“…Besides Cu SACs and Fe SACs, some other non-precious metal SACs are also well-developed for improving the benzene oxidation performance. [107][108][109] For example, Cao et al 110 reported a universal synthesis pathway for the fabrication of a series of SACs by using ionic liquids (ILs). To be specific, ILs and metal ions were first coordinated and then co-adsorbed on the surface of g-C 3 N 4 nanosheets in water.…”
Section: Perspectivementioning
confidence: 99%
“…Activated carbon (AC) materials are characterized by their high surface area, significant chemical stability, tunability of the surface and structure, and ease of production. They can be derived from biomass sources such as coconut shells [23], banana peel [24], straw [25], fungal mycelium [26],…”
Section: Introductionmentioning
confidence: 99%